2013
DOI: 10.1017/s0031182013001443
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combiningArtemisia annuaandCurcuma longaethanolic extracts in broilers challenged with infective oocysts ofEimeria acervulinaandE. maxima

Abstract: Due to an increasing demand for natural products to control coccidiosis in broilers, we investigated the effects of supplementing a combination of ethanolic extracts of Artemisia annua and Curcuma longa in drinking water. Three different dosages of this herbal mixture were compared with a negative control (uninfected), a positive control (infected and untreated), chemical coccidiostats (nicarbazin+narazin and, later, salinomycin), vaccination, and a product based on oregano. Differences in performance (weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
(66 reference statements)
0
5
0
Order By: Relevance
“… Eimeria tenella, Eimeria maxima, and Eimeria acervulina Improves feed conversion ratio and body weight gain. ( Del Cacho et al, 2010 ; Drăgan et al, 2010 , 2014 ; de Almeida et al, 2014 ; Kaboutari et al, 2014 ; Jiao et al, 2018 ) Leaf powder of A. annua Protects chickens from pathological symptoms and mortality associated with Eimeria tenella infection and reduces the lesion score, and fecal oocyst output. The leaf powder was more efficient than the essential oil, which could be due to a lack of artemisinin in the oil, and to the greater antioxidant ability of A. annua leaves than the oils.…”
Section: Phytochemical (Herbal) Remedies For Avian Coccidiosismentioning
confidence: 99%
“… Eimeria tenella, Eimeria maxima, and Eimeria acervulina Improves feed conversion ratio and body weight gain. ( Del Cacho et al, 2010 ; Drăgan et al, 2010 , 2014 ; de Almeida et al, 2014 ; Kaboutari et al, 2014 ; Jiao et al, 2018 ) Leaf powder of A. annua Protects chickens from pathological symptoms and mortality associated with Eimeria tenella infection and reduces the lesion score, and fecal oocyst output. The leaf powder was more efficient than the essential oil, which could be due to a lack of artemisinin in the oil, and to the greater antioxidant ability of A. annua leaves than the oils.…”
Section: Phytochemical (Herbal) Remedies For Avian Coccidiosismentioning
confidence: 99%
“…Another reported that curcumin (diferuloylmethane), an active compound in C. longa , consistently destroyed sporozoites of E. tenella [ 118 ]. Similarly, a combination of A. annua and C. longa showed anticoccidial efficacy in broilers challenged with a mixture of E. acervulina and E. maxima [ 119 ]. In addition, curcumin was shown to enhance coccidiosis resistance as evidenced by increased BW gains and reduced oocyst shedding and gut lesions [ 21 , 67 ].…”
Section: Plants and Compounds For Avian Coccidiosismentioning
confidence: 99%
“…The combination of plants extracts was also used to evaluate anticoccidial activity, with the aim of obtaining a higher activity. Almeida et al [ 81 ] combined Artemisia annua and Curcuma longa ethanolic extracts to treat broilers infected with E. acervulina and E. maxima . The activity of both extracts was compared with broilers treated with chemical coccidiostats as controls.…”
Section: Natural Alternatives To Controlling Coccidiosismentioning
confidence: 99%